2009
DOI: 10.1159/000204351
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the Educational Environment by Medical Students Undergoing a Curricular Transition in Kuwait

Abstract: Objective: The aim of this study was to measure the students’ perceptions of the educational environment in a medical school undergoing curricular transition from a traditional to a problem-based learning (PBL) program in the academic year 2006–2007. Materials and Methods: The Dundee Ready Education Environment Measure (DREEM) was used to evaluate perception of the educational environment. Multivariate logistic regression models were used to identify the factors related to educational environment perception th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
54
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 24 publications
14
54
2
2
Order By: Relevance
“…Under such circumstances, establishing a realistic time schedule is essential. Similar findings have been detected by several other research groups 16,30,31,39,46 and they think that the issue is attributable to poor coordination, underresourcing, and complicated scheduling.…”
Section: Specific Implicationssupporting
confidence: 88%
“…Under such circumstances, establishing a realistic time schedule is essential. Similar findings have been detected by several other research groups 16,30,31,39,46 and they think that the issue is attributable to poor coordination, underresourcing, and complicated scheduling.…”
Section: Specific Implicationssupporting
confidence: 88%
“…The only significant were item # 2 (table 2, and # 5 table # 3), which deal with adequacy and availability of library resources when students need them program has improve students' skills in communication respectively. This were obvious in the results of (15,21,22,24) The response about help and support for learning according to year, resources to support learning according to year (table 4 and Significant of the study materials and adequacy and availability of library resources, this was in agreements with the results of 16,17,19,21,22,23,24. Those demonstrated that graduated founded the needed material at the library each time they needed.…”
Section: Discussionsupporting
confidence: 76%
“…This is in parallel and strongly agreed with the finding of Nosair et al (16). But disagreed with Buhaimed et al (22), those concluded that, they should improve their educational environment in order to advance the quality of the delivered curriculum among their students.Students' perception of their educational environment was positive at both Rabigh and Jeddah campuses of King Abdulaziz University Imran et al (18). This totally agreed with our finding but disagreed with the study contacted by Al-Ayed et al (20) at King Saud University, this could be explained by the variety of programs and environment at KSU.…”
Section: Students Experience Survey About the Quality Of Learning At supporting
confidence: 71%